DESIGNING A LESSON PLAN FOR INDONESIAN ADULT STUDENTS BY USING TBLT (TASK BASED LANGUAGE TEACHING) - Muhammad Ahkam Arifin (Universitas Islam Negeri Alauddin Makassar, 2018)
This paper starts with the introduction concerning the development of the pedagogical implementation of second language acquisition (SLA) from communicative language teaching (CLT) to task based language teaching (TBLT). Within the same section, the definition of a task is also provided. It then continues to the design of the lesson plan by implementing the six-step model for TBLT as suggested by Nunan (24); the rationale for each of the step is presented. Lastly, it culminates with the evaluation over the principles applied in the design of the lesson plan.